Acute reduction in serum progesterone concentrations after feed intake in dairy cows - Vasconcelos, José Luiz Moraes [UNESP]; Sangsritavong, S.; Tsai, S. J.; Wiltbank, M. C. (Elsevier, 2003)
This study tested the hypothesis that high feed consumption will acutely decrease circulating progesterone concentrations. In the first experiment, a Latin Square design was used to test whether feeding pattern would alter circulating progesterone in pregnant lactating Holstein cows (n = 12). Feed was removed for 12 h before the experiment and cows were then either fed 100% of the total mixed ration (TMR), 50% of TMR every 12 h, 25% of TMR every 6 h, or left unfed for an additional 12 h. Blood samples were taken every hour for 24 h. Provision of 100 or 50% of TMR decreased circulating progesterone by 1 h after feeding and progesterone remained depressed until 8-9 h after feeding. Feeding 25% of TMR did not reduce circulating progesterone concentrations. Experiment 2 used a crossover design to measure the effect of acute feeding on circulating progesterone and LH concentrations during delivery of a constant amount of exogenous progesterone (Eazi-Breed CIDRs) in lactating Holstein cows (n = 8) and nonpregnant dry Holstein cows (n = 6). Blood samples were taken every 15 min for 8 h. There was no change in serum progesterone during the 8 h treatment period in unfed cows; however, feeding decreased (P < 0.05) circulating progesterone between 2 and 6 h after feeding. In lactating cows, feeding increased mean LH (P < 0.05). There were more LH pulses (P = 0.01) in lactating than nonlactating cows. Thus, acute feeding reduced circulating progesterone in pregnant lactating cows apparently due to an increase in progesterone metabolism. Interestingly, feeding multiple smaller meals eliminated the acute effect of feeding on circulating progesterone. © 2003 Published by Elsevier B.V.
Keywords: Dairy cows; LH; Nutrition; Progesterone; luteinizing hormone; progesterone; animal; blood; cattle; eating; female; food; kinetics; lactation; pregnancy; Animals; Cattle; Eating; Female; Food; Kinetics; Lactation; Luteinizing Hormone; Pregnancy